2013
DOI: 10.1371/journal.pone.0062471
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET and MRI in Logopenic Primary Progressive Aphasia versus Dementia of the Alzheimer’s Type

Abstract: ObjectivesThe logopenic variant of primary progressive aphasia is an atypical clinical variant of Alzheimer’s disease which is typically characterized by left temporoparietal atrophy on magnetic resonance imaging and hypometabolism on F-18 fluorodeoxyglucose positron emission tomography. We aimed to characterize and compare patterns of atrophy and hypometabolism in logopenic primary progressive aphasia, and determine which brain regions and imaging modality best differentiates logopenic primary progressive aph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 39 publications
8
77
1
3
Order By: Relevance
“…Based on previous neuroimaging studies (Rabinovici et al, 2008;Madhavan et al, 2013;Teichmann et al, 2013;Rogalski et al, 2014;Ossenkoppele et al, 2015a) and the specific language presentation, we hypothesized that patients with logopenic variant PPA would show 18 F-AV1451 uptake in temporoparietal language regions in a clearly asymmetric fashion with greater tau in the left hemisphere compared to right hemisphere. Visual inspection of individual images and a quantitative laterality index indicated that three logopenic variant PPA showed the predicted left 4 right pattern, one was fairly symmetric and one patient had greater 18 F-AV1451 uptake in right than in left hemisphere.…”
Section: Distinct Variants Of Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous neuroimaging studies (Rabinovici et al, 2008;Madhavan et al, 2013;Teichmann et al, 2013;Rogalski et al, 2014;Ossenkoppele et al, 2015a) and the specific language presentation, we hypothesized that patients with logopenic variant PPA would show 18 F-AV1451 uptake in temporoparietal language regions in a clearly asymmetric fashion with greater tau in the left hemisphere compared to right hemisphere. Visual inspection of individual images and a quantitative laterality index indicated that three logopenic variant PPA showed the predicted left 4 right pattern, one was fairly symmetric and one patient had greater 18 F-AV1451 uptake in right than in left hemisphere.…”
Section: Distinct Variants Of Alzheimer's Diseasementioning
confidence: 99%
“…Among many other applications, amyloid-b imaging has been incorporated into diagnostic criteria for various stages of the disease (Albert et al, 2011;McKhann et al, 2011;Sperling et al, 2011;Dubois et al, 2014), has substantial impact on clinical decision-making (Ossenkoppele et al, 2013a;Sanchez-Juan et al, 2014) and patient management plans (Schipke et al, 2012;Grundman et al, 2013), and has shown potential as a surrogate outcome measure in clinical trials tailored to reduce cerebral amyloid-b plaque burden (Salloway et al, 2014;Liu et al, 2015). A yet unresolved issue after a decade of amyloid-b imaging research, however, is the disconnection between the diffuse distribution of amyloid-b pathology throughout the neocortex (Rabinovici et al, 2010;Wolk et al, 2012;Lehmann et al, 2013;Jung et al, 2015) and the selective patterns of brain atrophy and glucose hypometabolism that strongly correlate with clinical symptoms (Rabinovici et al, 2010;Ridgway et al, 2012;Lehmann et al, 2013;Madhavan et al, 2013). Thus, although amyloid-b deposition may be a prerequisite to developing Alzheimer's disease dementia, at some point during the disease course additional factors are likely involved in determining regional neurodegeneration and symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…The main regions of involvement in PCA include the occipital, parietal, and occipito-temporal regions [17, 19], while those affected in lvPPA include the posterior portions of the superior and middle temporal lobe, the inferior parietal lobe, and the temporo-parietal junction [20, 21]. Patterns of neurodegeneration are usually asymmetric in lvPPA, involving the left hemisphere greater than right, and can also be asymmetric in PCA [22], more commonly involving the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Ce pattern est comparable à celui retrouvé dans les cas de maladie d'Alzheimer typique (amné sique au stade dé mentiel) à pré dominance gauche [68,71]. L'atteinte temporale externe et frontale infé rieure gauche est cependant plus importante dans l'aphasie progressive primaire logopé nique ce qui permettrait une bonne façon de distinguer ces deux entité s [72]. Il en est de mê me pour les atrophies corticales posté rieures [73] malgré des zones de chevauchement de l'atrophie dans le carrefour parié totemporal gauche [61,74].…”
Section: Irmunclassified
“…Ceci permet de le diffé rencier des autres types d'APP ayant des atteintes plus anté rieures, à l'exception du type fluent anomique, correspondant probablement à une forme prodromique des diffé rentes formes d'APP [86]. Ce pattern permet aussi de bien diffé rencier l'APP logopé -nique de la maladie d'Alzheimer typique (amné sique au stade dé mentiel) [72,87]. Par ailleurs, l'imagerie nuclé aire type PET ou SPECT est plus fré quemment contributive pour mettre en é vidence une anomalie du carrefour parié totemporal gauche né cessaire au diagnostic que l'imagerie anatomique type IRM (86 à 90 % vs 57 à 60 %) [34,88].…”
Section: Imagerie Nucléaireunclassified